Efficacy and Safety of Ruxolitinib in Patients with Myelofibrosis: A Retrospective and Multicenter Experience in Turkey - Turgut, Mehmet; Soyer, Nur; Ali, Rıdvan; Haznedaroğlu, İbrahim; Yılmaz, Fergun; İlhan, Gül; Cömert, Melda; Aslaner, Müzeyyen; İnce, İdris; Yavaşoğlu, İrfan; Özdemirkıran, Füsun; Özet, Gülsüm; et al. (TÜBİTAK Scientific & Technological Research Council Turkey, 2021)
Background/aim: The aim of this study is to assess the efficacy and safety of ruxolitinib in patients with myelofibrosis. Materials and methods: From 15 centers, 176 patients (53.4% male, 46.6% female) were retrospectively evaluated. Results: The median age at ruxolitinib initiation was 62 (28-87) and 100 (56.8%) of all were diagnosed as PMF. Constitutional symptoms were observed in 84.7%. The median initiation dose of ruxolitinib was 30 mg (10-40). Dose change was made in 69 (39.2%) patients. Forty seven (35.6%) and 20 (15.2%) of 132 patients had hematological and nonhematological adverse events, respectively. The mean spleen sizes before and after ruxolitinib treatment were 219.67 +/- 46.79 mm versus 199.49 +/- 40.95 mm, respectively (p < 0.001). There was no correlation between baseline features and subsequent spleen response. Overall survival at 1-year was 89.5% and the median follow up was 10 (1-55) months. We could not show any relationship between survival and reduction in spleen size (p = 0.73). Conclusion: We found ruxolitinib to be safe, well tolerated, and effective in real-life clinical practice in Turkey. Ruxolitinib dose titration can provide better responses in terms of not only clinical benefit but also for long term of ruxolitinib treatment.
Q4
SCI-Expanded
Soyer, Nur/0000-0002-7722-506X; Yilmaz, Fergun/0000-0001-5118-6894; Durusoy, Raika/0000-0003-1041-8462; Guvenc, Birol/0000-0001-7641-5673; Karakuş, Volkan/0000-0001-9178-2850; Özgür, Gökhan/0000-0003-0357-0503; Kis, Cem/0000-0001-7423-7180; Sahin, Fahri/0000-0001-9315-8891; Kaya, Emin/0000-0001-8605-8497; Haznedaroglu, Ibrahim C/0000-0001-8028-9462;
Keywords: Myelofibrosis; Treatment; Survival; Ruxolitinib; Adverse Events; General & Internal Medicine